Improved Biomass Cookstove Use in the Longer Run : Results from a Field Experiment in Rural Ethiopia - Mekonnen, Alemu; Beyene, Abebe D.; Bluffstone, Randall; Dissanayake, Sahan; Gebreegziabher, Zenebe; LaFave, Daniel; Martinsson, Peter; Toman, Michael A. (World Bank, Washington, DC, 2020)
This paper reports on electronically-monitored improved use of the "Mirt" biomass stove in Ethiopia over a relatively long period of three-and-a-half years, using stove use data collected at five points in time. The results show that 62 percent of the households surveyed still retained their stoves after more than three years, which is a low level of abandonment, as the lifetime of the Mirt stove is approximately five years. Dis-adoption of the stove is not correlated with any of three monetary incentives provided at the time of distribution. With and without adjusting for dis-adoption, no longer-run differences in stove retention are found across treatments. Among those who retained their stoves, average regular stove use increased over time, but generally it is statistically the same toward the end of the first year. Thus, despite the relatively long timeframe, no decline is observed in regular usage. Comparing the persistence of the treatment effects, the paper finds that, in the longer run, subsidizing the cost most effectively promotes increased regular use over time.